3-49 - i = -i 1 = 10.667 A , from fig. (b), v = i 3-3i 1 =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Chapter 3, Solution 49 For the supermesh in figure (a), 3i 1 + 2i 2 – 3i 3 + 16 = 0 (1) At node 0, i 2 – i 1 = 2i 0 and i 0 = -i 1 which leads to i 2 = -i 1 (2) For loop 3, -i 1 –2i 2 + 6i 3 = 0 which leads to 6i 3 = -i 1 (3) Solving (1) to (3), i 1 = (-32/3)A, i 2 = (32/3)A, i 3 = (16/9)A
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: i = -i 1 = 10.667 A , from fig. (b), v = i 3-3i 1 = (16/9) + 32 = 33.78 V . + 1 i 1 + v or + v i 2 2 16V 2 (b) 3 i 1 2 i 1 i 2 i 3 2 1 + 16 V 0 i 2 2i 0 (a)...
View Full Document

This note was uploaded on 08/27/2011 for the course EEL 3111C taught by Professor Srivastava during the Spring '08 term at University of Florida.

Ask a homework question - tutors are online